Silsilah Dan Perkembangan Kerajaan Kutai Kartanegara (1300-1732) - Sopian, Hendi; Norhidayat, Norhidayat (History Education Department, Universitas Mulawarman, 2022)
The Kutai Kartanegara kingdom was originally located in Jaitan Layar, Kutai Lama village, Anggana District, the founding of the Kutai Kartanegara kingdom in 1300 AD, the first king of the Kutai Kartanegara kingdom was Aji Batara Agung Dewa Sakti, during the time of the first king the kingdom of the Kutai Kartanegara Kingdom began to be heard by outsiders , because he often visits Majapahit. Judging from its history, there are many factors that led to the establishment and development of the Kutai Kartanegara kingdom that cannot be explained clearly and scientifically. This research answers the problem formulation of the genealogy of the Kutai kingdom and how it developed. This study used descriptive qualitative method. This method is a research method that utilizes qualitative data and is described descriptively. This type of qualitative descriptive data analysis is often used to analyze social events, phenomena and situations. The results of this research explain the birth of the Kutai Kartanegara kingdom, the development of the Kutai Kartanegara kingdom, starting from Aji Batara Agung Dewa Sakti to Aji Pangeran Dipati Anum and explain things that happened during the reign of the Kutai Kartanegara kings.